Camundongos C57BL/6 apresentam maior índice de reabsorção fetal durante infecção por Toxoplasma gondii em comparação com camundongos BALB/c - Coutinho, Loyane Bertagnolli (2010)
The Toxoplasma gondiii infection during pregnancy is associated with adverse pregnancy outcome. Groups of C57BL/6 and BALB/c females were orally infected with 5 cysts of ME49 strain of T. gondii on day 1 of pregnancy and sacrificed on days 8 and 19 after. Another group was infected on day 14 of pregnancy and sacrificed 5 days later. The females were evaluated for resorption ratio, tissue parasitism, expression of iNOS by immunohistochemistry and inflammatory changes in the uterus/placenta, lungs and CNS. It was observed that only one C57BL/6 from 9 pregnant and infected animals presented fetuses on day 19 of pregnancy and infection, meaning high resorption rate. This lineage of mice also presented higher leukocyte infiltration in the uterus and inflammatory changes in the lung on day 8 of pregnancy and infection, and higher inflammatory changes in the CNS on day 19 of pregnancy and infection when compared to BALB/c mice. In addition, some females of the C57BL/6 mice presented necrotic foci in the implantation sites on day 8 of pregnancy and infection. Furthermore, C57BL/6 mice showed higher number of parasites in the lungs on day 8 of pregnancy and infection and in the CNS on day 19 of pregnancy and infection compared to BALB/c mice. However, the parasite was seldom found in the uterus and placenta in both lineages of mice irrespective of the day of infection. C57BL/6 mice also demonstrated higher mast cell infiltration and higher degranulation index on day 19 of pregnancy and infection, compared to BALB/c mice. C57BL/6 presented higher interferon- γ (IFN-γ and tumor necrosis factor (TNF) levels in serum samples on day 8 of pregnancy and infection and lower interleukin-10 (IL-10) levels on day 19 of pregnancy and infection compared to BALB/c mice. Concerning iNOS expression, there was no difference in the enzyme expression between C57BL/6 and BALB/c lineages on day 8 or 19 of pregnancy and infection, indicating that iNOS is not related to the occurrence of abortion. Our data suggest that the worst pregnancy outcome observed in C57BL/6 mice could be associated to the higher inflammatory alterations in the uterus/placenta and higher proinflammatory cytokine levels systemically better than presence of the parasite in this site of infection. Additionally, the major impaired pregnancy outcome occurs when the infection happens in the early phase of the pregnancy, and this result is related to the genetic background of mice, being the C57BL/6 more susceptible than BALB/c mice.